AKTIVITAS ANTIBAKTERI DARI FUNGI ENDOFIT Caulerpa racemosa ASAL PERAIRAN PULAU LEMUKUTAN (ANTIBACTERIAL ACTIVITY FROM ENDOPHYTIC FUNGI Caulerpa racemosa ORIGIN IN LEMUKUTAN ISLAN WATERS) - Melia Trianasta; Warsidah Warsidah; Mega Sari Juane Sofiana (Indonesian Journal of Pure and Applied Chemistry, 2021)
Green macroalgae Caulerpa racemosa from the waters of Lemukutan Island was isolated to obtain its endophyte fungi. Endophyte fungi were explored to determine their potential as antibacterial. Isolation of endophyte fungi was carried out by dilution method using PDA media. Endophyte fungi with different morphology were obtained as many as 4 isolates, named CRF1, CRF2, CRF3 and CRF4. Antibacterial activity testing was carried out by agar diffusion method. Endophyte fungi isolate CRF3 showed the best activity against Escherichia coli bacteria while CRF2 isolate showed the best activity against Staphylococcus aureus with inhibition zone diameters of 15.83 mm and 11.99 mm, respectively. Keywords:Endophyte Fungi, Caulerpa racemosa, Antibacterial, Lemukutan